2018
DOI: 10.1186/s12879-018-3371-7
|View full text |Cite
|
Sign up to set email alerts
|

Relapse of chronic melioidosis in a paediatric cystic fibrosis patient: first case report from Malaysia

Abstract: BackgroundBurkholderia pseudomallei is the causative agent of melioidosis, which is a potentially life threatening disease endemic in Southeast Asian countries. In Malaysia, cystic fibrosis (CF) is an uncommon condition. The association between CF and B.pseudomallei infections has been reported previously. However, this is the first case report of a pediatric melioidosis relapse and co-infection with other Gram-negative bacteria in Malaysia.Case presentationA 14-year-old Chinese Malaysian boy presented with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Infection is acquired through direct inoculation, inhalation, or ingestion of contaminated soil or water with an incubation period of 1 to 21 days (4-10). The typical presentation with melioidosis in adults is pneumonia, which ranges from mild disease to subacute pulmonary disease mimicking tuberculosis to fulminant septic shock (4)(5)(6)(7)(8)(9)(10). Extrapulmonary presentations such as cutaneous infections, septic arthritis, genitourinary infections, and encephalitis have been reported (4)(5)(6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection is acquired through direct inoculation, inhalation, or ingestion of contaminated soil or water with an incubation period of 1 to 21 days (4-10). The typical presentation with melioidosis in adults is pneumonia, which ranges from mild disease to subacute pulmonary disease mimicking tuberculosis to fulminant septic shock (4)(5)(6)(7)(8)(9)(10). Extrapulmonary presentations such as cutaneous infections, septic arthritis, genitourinary infections, and encephalitis have been reported (4)(5)(6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…This is followed by an eradication phase, which consists of 3 to 6 months of oral antimicrobials. Trimethoprim-sulfamethoxazole is the drug of choice for eradication, but amoxicillin-clavulanic acid and doxycycline are alternatives (4)(5)(6)(7)(8)(9)(10). Mortality is high in melioidosis associated with sepsis (50% to 90%) despite adequate treatment (10).…”
Section: Discussionmentioning
confidence: 99%
“…There was also a report of a diabetic patient who worked as a palm oil worker in Perak, being infected with melioidosis, tuberculosis and Salmonella at the same time, suggesting diabetes as a predisposing factor to multiple infections (Sulaiman et al, 2013). Recorded risk factors for melioidosis include co-morbidities, immune-compromission, cystic fibrosis (Mariappan et al, 2018), thalassemia, kwashiorkor, albinism and patent ductus arteriosus (Fong et al, 2015). Residing areas also play an important role in acquiring melioidosis, Abu Hassan et al (2019) showed that living in areas with large-scale irrigation-based agriculture and mixed agriculture/pastoral environments had a higher prevalence rate of melioidosis (Abu Hassan et al, 2019).…”
Section: Melioidosismentioning
confidence: 99%